Quercetin Supplementation in Andromed Extender on Quality of Boer Goat Semen during Room Temperature Storage - Madhyastha, Wandha; Nugraha, Chairdin Dwi; Suyadi, Suyadi (Jurnal Ilmu Peternakan Terapan, 2024)
This research aimed to determine the effect of quercetin antioxidant concentration levels on Boer goat semen quality during room temperature storage using andromed extender. Fresh semen was collected from two of 5-years-old Boer goats with weight of 60 and 70 kg. The method of this research was an experimental laboratory using Completely Randomized Design (CRD) Factorial of two factors, namely the treatment of quercetin concentration levels at 0 µM, 10 µM, 20 µM and 30 µM and the storage time during room temperature at 0 hour, 2 hours, 4 hours, 6 hours and 8 hours. The variables were observed based on individual motility, viability, abnormalities and membrane integrity of spermatozoa. The result showed that the antioxidant quercetin 30 µM have a significant effect to individual motility (P<0.05) but did not have a significant effect to the viability and abnormality of spermatozoa. Antioxidant quercetin gave a highly significant difference on membrane integrity (P<0.01). Storing semen at room temperature for 6 hours resulted in a highly significant difference in individual motility, abnormality and membrane integrity (P<0.01) but did not show a significant difference to viability. The best result showed that the antioxidant quercetin 30 µM was able to maintain the quality of spermatozoa at room temperature storage up to 6 hours.